The Relationship Between Knowledge About Balanced Nutrition Guidelines And The Amount Of Pocket Money With Overnutritional Status Of Adolescents - Kurnia Dewi, Emilia; Warajati Kisnawaty, Sudrajah; Ria Rakhma, Luluk (JURNAL KESMAS DAN GIZI (JKG), 2025)
The nutritional status of adolescents is currently a major public health concern, particularly due to the increase in cases of overweight and obesity, which increase the risk of non-communicable diseases (NCDs) such as diabetes mellitus, hypertension, and heart disease. The main factors influencing nutritional status are a balanced diet and adequate physical activity. However, other factors such as knowledge of balanced nutrition guidelines and pocket money management also play an important role. Nutrition knowledge is expected to influence attitudes and healthy food choices, while higher pocket money amounts may increase the tendency to purchase high-calorie, low-nutrient foods, thereby contributing to the risk of overweight. This study aims to analyze the relationship between knowledge of balanced nutrition guidelines and pocket money with nutritional status among high school students at SMA IT Nur Hidayah Sukoharjo. A cross-sectional observational study design was used with a population of all 11th grade students (N=283). The study sample consisted of 72 students, selected through simple random sampling. Data analysis used the Pearson product moment statistical test for nutrition knowledge and the Spearman rank test for pocket money,following the Kolmogorov-Smirnov normality test. The results showed no significant relationship between knowledge of balanced nutrition guidelines and overweight status among adolescents (p=0.676). However, there was a significant relationship between the amount of pocket money and overweight status among adolescents (p=0.043). This indicates that nutrition knowledge is not a direct factor influencing overweight status, while a higher amount of pocket money is correlated with the risk of overweight due to excessive consumption patterns. Teenagers are advised to increase their knowledge and application of balanced nutrition in their daily lives and to use their pocket money wisely when buying food and drinks.